Critical analysis on the practices of family takaful and life insurance products in Malaysia - Wan Reena Zahirah (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2012)
This paper discusses about the differences and similarities in the Malaysian practice of individual family takaful product and conventional individual life insurance product between the takaful operators and insurance companies. The motivation of this research is to help the consumers and the industry to better understand the similarities and differences of the development processes and the operations of the takaful and insurance products. Since some claimed that the conventional insurance practice is not entirely unlawful. the researcher believed that there is a need to critically review takaful products and make a comparison with insurance products from the product development process until the maturity and seek the opinions of shari 'ah scholars on the differences of the practices between takaful and insurance company. This paper is also expected to make the public fully understand the reason behind the shuri ·ah cornpliancy and non-compliancy of a certain contract and operating process of the products so that the contemporary Muslim Ummah can gain benefits from it. The statistical methods that the researcher uses in this research are descriptive analysis and content analysis due to the fact that the research is more inclined towards qualitative rather than quantitative. The outcome of this research shows that there are some significance differences in the operations of the products which will potentially enlighten the public. Nonetheless, more in-depth research could be undertaken by analyzing and contrasting other intriguing products that are more complex to be undisputable regarding the differences between takaful and insurance products.